Speech and hearing screening camps and exhibitions - MG, Subramanyam; HS, Satyam (Journal of All India Institute of Speech and Hearing)
To educate the public speech and hearing screening camps and exhibitions were conducted. Hitherto seven camps and eight exhibitions have been conducted at different places of southern Mysore state. The need for such camps and exhibitions and details about these camps have been discussed